2018
DOI: 10.3390/foods7100174
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Artificial LED Light and Far Infrared Irradiation on Phenolic Compound, Isoflavones and Antioxidant Capacity in Soybean (Glycine max L.) Sprout

Abstract: The effect of light emitting diode (LED) light and far infrared irradiation (FIR) on total phenol, isoflavones and antioxidant activity were investigated in soybean (Glycine max L.) sprout. Artificial blue (470 nm), green (530 nm) LED and florescent light (control) were applied on soybean sprout, from three to seven days after sowing (DAS) in growth chamber. The photosynthetic photon flux density (PPFD) and photoperiod was 150 ± 5 μmol m−2s−1 and 16 h, respectively. The FIR was applied for 30, 60 and 120 min a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 25 publications
5
30
0
Order By: Relevance
“…A different study showed that natural light yielded greater chlorophyll and total carotenoid contents in V. unguiculata seedlings than irradiation with blue, yellow, and red LED light [60]. Azad et al [61] reported that soybean sprouts grown under green LED treatment presented higher isoflavone contents and higher phenolic contents than sprouts grown under florescent light, and far-infrared irradiation (FIR) increased the total phenolic content and total isoflavones content in soybean sprouts. Additionally, UV-B irradiation at low dosages induced anthocyanin production in radish sprouts [62], and UV-C irradiation at relatively high dosages significantly increased total phenolic content, total flavonoid content, and proanthocyanidins in lemon pomace dried powder [63].…”
Section: Discussionmentioning
confidence: 99%
“…A different study showed that natural light yielded greater chlorophyll and total carotenoid contents in V. unguiculata seedlings than irradiation with blue, yellow, and red LED light [60]. Azad et al [61] reported that soybean sprouts grown under green LED treatment presented higher isoflavone contents and higher phenolic contents than sprouts grown under florescent light, and far-infrared irradiation (FIR) increased the total phenolic content and total isoflavones content in soybean sprouts. Additionally, UV-B irradiation at low dosages induced anthocyanin production in radish sprouts [62], and UV-C irradiation at relatively high dosages significantly increased total phenolic content, total flavonoid content, and proanthocyanidins in lemon pomace dried powder [63].…”
Section: Discussionmentioning
confidence: 99%
“…Monochromatic red LED stimulated anthocyanin accumulation in Malus domestica Borkh more significantly than monochromatic blue LED, which has been identified as due to an increased expression of anthocyanin synthesis gene ( MdMYB10 and MdUFGT gene) under the influence of the red LED [ 29 ]. The phenol content, total isoflavones, and antioxidant capacity of soybean germ when grown under LED blue light (470 nm) were also higher than those of LED green (530 nm) and florescent light [ 30 ]. LED blue light (440–540 nm, peak wavelength of 469 nm) had a positive impact on A. roxburghii [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that FIR increases the quantities of nutraceutical compounds, while improving antioxidant property, anti-inflammatory, and inhibitory activity in the A549 Cell line in Chrysanthemum indicum L. [11]. In particular, FIR enhances phenolic content and antioxidant capacity of buckwheat flour [12], sprouting bean flour [13], citrus cack [14], and rice hull [15]. However, to the best of our knowledge, there are no reports published on the effect of FIR on nutraceutical compounds in AGN.…”
Section: Introductionmentioning
confidence: 99%